Modeling of laser-driven proton radiography of dense matter - Kar, S; Borghesi, M; Audebert, P; Benuzzi-Mounaix, A; Boehly, T; Hicks, D; Koenig, M; Lancaster, K; Lepape, S; Mackinnon, A; Norreys, P; Patel, P; et al. (2008)
Laser-driven MeV proton beams are highly suitable for quantitative diagnosis of density profiles in dense matter by employing them as a particle probe in a point-projection imaging scheme. Via differential scattering and stopping, the technique allows to detect density modulations in dense compressed matter with intrinsic high spatial and temporal resolutions. The technique offers a viable alternative/complementary route to more established radiographic methods. A Monte-Carlo simulation package, MPRM, has been developed in order to quantify the density profile of the probed object from the experimentally obtained proton radiographs. A discussion of recent progress in this area is presented on the basis of analysis of experimental data, which has been supported by MPRM simulation. © 2008 Elsevier B.V. All rights reserved.